A new host record of Yunnanensis phragmitis on white ginger lily (Hedychium coronarium J. Koenig.) from China - Tan, Xiao-Ming; Li, Cui; Hu, Dian-Ming; Tennakoon, Danushka S.; Song, Hai-Yan (Phytotaxa, 2024)
Hedychium coronarium, commonly known as “white ginger lily or garland flower” is a perennial flowering plant in the family Zingiberaceae. There is a limited number of studies associated with Hedychium-associated fungi in China. During a fungal diversity survey, a saprobic member of Dothideomycetes was collected from dead stem of H. coronarium in Kunming, China. Morphological characteristics coupled with combined gene analysis of LSU, SSU, ITS and tef1-α sequence data, showed it is Yunnanensis phragmitis, which is introduced as a new host record in this paper. Maximum likelihood and Bayesian inference analyses were performed to clarify the phylogenetic affinities of the species. Our collection is compared with the type of Y. phragmitis and a comprehensive description and micrograph are provided.